2015
DOI: 10.1002/glia.22809
|View full text |Cite
|
Sign up to set email alerts
|

From demyelination to remyelination: The road toward therapies for spinal cord injury

Abstract: Myelin integrity is crucial for central nervous system (CNS) physiology while its preservation and regeneration after spinal cord injury (SCI) is key to functional restoration. Disturbance of nodal organization acutely after SCI exposes the axon and triggers conduction block in the absence of overt demyelination. Oligodendrocyte (OL) loss and myelin degradation follow as a consequence of secondary damage. Here, we provide an overview of the major biological events and underlying mechanisms leading to OL death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 347 publications
(407 reference statements)
0
99
0
Order By: Relevance
“…As in the present study, only dogs presenting acute severe motor function impairment due to a different pathogenesis were enrolled, the differences of CLR, T2W‐LER, and T2WLR values between Grade IV and V could be too low to detect a significant correlation with TMMEPs during therapy monitoring. A correlation of MRI measurements and TMMEPs both obtained at 2nd follow‐up examination was not expected, because absence of compression and persistence of focal spinal cord hyperintensities do not reflect microstructural processes, which contribute to functional motor recovery …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the present study, only dogs presenting acute severe motor function impairment due to a different pathogenesis were enrolled, the differences of CLR, T2W‐LER, and T2WLR values between Grade IV and V could be too low to detect a significant correlation with TMMEPs during therapy monitoring. A correlation of MRI measurements and TMMEPs both obtained at 2nd follow‐up examination was not expected, because absence of compression and persistence of focal spinal cord hyperintensities do not reflect microstructural processes, which contribute to functional motor recovery …”
Section: Discussionmentioning
confidence: 99%
“…Remyelination arises from resident glial progenitor cells, infiltrating the injured region, where they differentiate into oligodendrocytes producing myelin . Additionally, PNS associated Schwann cells migrate to the spinal cord lesion, contributing to remyelination by expressing platelet derived growth factor receptor α . These processes start immediately after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, traumatic paraplegia by severance of the spinal cord (SC) remains an irreversible condition. Basically, current clinical treatment strategies are targeted to promote axon regeneration and outgrowth beyond the scar formation following SC avulsion [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18][20][21][24][25][26][27][28][29][30][31][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Previous experimental and clinical studies together with GB have aroused some hope that paraplegic patients might achieve some selective voluntary muscle reinnervation after grafting the first motor neuron to skeletal hip muscles [10,11,25,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Demyelination occurs secondarily following spinal cord injuries [23], and although remyelination can occur on spared axons, it is insufficient to fully restore function [24]. In recent years a number of intrinsic and extrinsic factors have been identified that can influence remyelination efficiency, offering the possibility to use this knowledge to develop therapeutic interventions [25].…”
Section: Introductionmentioning
confidence: 99%